A Rare Case of Serous Papillary Ovarian Epithelial Type Carcinoma in Testis: A Rare Testicular Neoplasm - Alireza Abdollahi; Fereshteh Ensani; Mohsen Ayati; Sepideh Jahanian; Arezoo Eftekhar-Javadi; Atieh Khorsand (Journal of Family and Reproductive Health, 2019)
Ovarian epithelial type carcinomas of testis are an extremely rare group of tumors, a few cases of which having been reported. We present the case of a 67-year-old man, presented with testicular mass and inflation, who underwent radical orchiectomy and pathological and immunohistochemical assessments revealed serous papillary carcinoma of ovarian epithelial type tumor of testis.